Perceived Teaching Creativity and Strategy of Implementation in Distance Learning Activities - Widiningsih, Made Adrina; Artini, Luh Putu; Utami, Ida Ayu Made Istri (International Journal of Language and Literature, 2023)
Distance learning has been implemented in many schools due to covid-19. But it is still unknown whether teachers integrate creativity in learning still needs to be investigated. Therefore the aims of this study are to analyze how the teachers perceived their own creativity in teaching in the classroom. Then how they implanted in distance learning and analyze there is the discrepancy occurred between how the teachers’ perception toward their creativity and the facts of how the teachers implemented their creativity in the real teaching. Mix method was employed as the design of this study which meant there were primary and supportive data. The qualitative data was dominant than quantitative data. The setting of this study was in senior high school and two English teachers selected as the subject of this study. Self-rated questionnaire and classroom observation sheet were used as the instruments. The result of study showed that the teachers perceived themselves as creative, however, the teachers’ creativity was classified in slightly creative based on the observation. Those data demonstrated that there was the discrepancy between the teachers’ perception toward their creativity in the class. The implication of this research is the creativity in distance learning requires more than teachers' willingness, it also requires students' financial support.